Particular difficulties faced by GPs with young adults who will attempt suicide: a cross-sectional study - Younes, Nadia (BioMed Central, 2013)
BACKGROUND: Suicide is a major public health problem in young people. General Practitioners (GPs) play a central role in suicide prevention. However data about how physicians deal with suicidal youths are lacking. This study aims to compare young adult suicide attempters (from 18 to 39 years old) with older adults in a primary care setting. METHODS: A cross-sectional study was carried. All suicide attempts (N=270) reported to the French Sentinel surveillance System from 2009 to 2011 were considered. We conducted comparison of data on the last GP’s consultation and GPs’ management in the last three months between young adults and older adults. RESULTS: In comparison with older adults, young adults consulted their GP less frequently in the month preceding the suicidal attempt (40.9 vs. 64.6%, p=.01). During the last consultation prior to the suicidal attempt, they expressed suicidal ideas less frequently (11.3 vs. 21.9%, p=.03). In the year preceding the suicidal attempt, GPs identified depression significantly less often (42.0 vs. 63.4%, p=.001). In the preceding three months, GPs realized significantly less interventions: less psychological support (37.5 vs. 53.0%, p=.02), prescribed less antidepressants (28.6 vs. 54.8%, p<.0001) or psychotropic drugs (39.1 vs. 52.9%, p=.03) and made fewer attempts to refer to a mental health specialist (33.3 vs. 45.5%, p=.05). CONCLUSION: With young adults who subsequently attempt suicide, GPs face particular difficulties compared to older adults, as a significant proportion of young adults were not seen in the previous six months, as GPs identified less depressions in the preceding year and were less active in managing in the preceding three months. Medical training and continuing medical education should include better instruction on challenges relative to addressing suicide risk in this particular population.